Single and double electron capture in p-He and α-He collisions. (28th February 2017) - Samaddar, S; Halder, S; Mondal, A; Mandal, C R; Purkait, M; Das, T K
Abstract: The differential and total cross sections for both single and double electron capture in collisions of H + and He 2+ with ground state helium atom have been studied by means of the four-body model of target continuum distorted wave (TCDW-4B) approximation in the energy range from 30 to 1000 keV amu –1 . In this model, distortion in the final channel related to the Coulomb continuum states of the active electron(s) in the field of residual target ion are included. The calculations are based on the independent electron model. The present computed results are compared with the available experimental and other theoretical results. Total cross sections are found to be in good agreement with the measurements. We have also analysed differential cross sections (DCS) for both single and double electron capture in the collision of proton and α -particles with helium atoms at different projectile energies. The present DCS data exhibits the typical steeply decreasing dependence on the projectile scattering angles, but neither oscillating structures characteristic of interference effects nor peaks reminiscent of the Thomas peak are observed at different projectile energies. The obtained results for the DCS into the ground state are compared with the experimental data and overall a satisfactory agreement has been found. Finally we have also studied the variation of double to single capture differential cross-section ratios with projectile scattering angles at different impact energies.